Eruption Time of Permanent Teeth in Pakistani Children - N Khan (Iranian Journal of Public Health, 2011)
Background: To determine the mean eruption time of permanent teeth of Pakistani children and to evaluate the effects of gender, type of schools, height, weight and body mass index on it. Methods: This cross sectional study was conducted from September 2007 to April 2008.  4370 children of ‘just erupted' teeth were obtained from 102 randomly selected schools from 18 towns of Karachi, using systematic random sampling procedure. The dental examination was carried out for the selected child. Height, weight and date of birth were also obtained. Two sample‘t' test and paired ‘t' test were employed to compare the mean time of eruption between gender and type of schools (private/ public),  and upper and lower jaws. Pearson and partial correlations were used to determine the significant relationship between eruption time with height, weight and BMI. Results: The right first molars of upper and lower jaws showed the minimum eruption time. Second molars were the last tooth to emerge. Only 3 teeth showed significant difference of eruption time between the genders. None of contralateral teeth showed any statistical significant difference. All the mandible teeth, except the premolars, erupted earlier than maxillary teeth. Private schools children showed early eruption than the public schools children. The Pearson and partial correlation were significant positively correlated with height.  Eruption time of all the teeth, except one, showed positive correlation with weight. Conclusion: The eruption time of Pakistani children are different in many aspects with to other nationalities.